Áreas verdes em Teresina-PI: aspectos legais, ambientais e de gestão - Carvalho, Andrea Melo de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
There are many green areas in Teresina/PI called environmental parks: forests or orchards. They are important instruments for environmental conservation and improvements in the urban climate, but most of these areas are abandoned by the government and the population surrounding it, which is caused mainly because of the inapplicability of local legislation about green areas either to the creation or maintenance of the parks. In general, they are indiscriminately created and do not have a land-use plan for their management. There are no incentives for environmental education of the surrounding population and it has led to the degradation of the environmental parks - manifested mainly through pollution and government usage of these lands for housing purposes. For better understanding of the subject, this thesis sought to analyze the origin of the environmental parks throughout history. Then it focused on related legislation. Finally, it pointed out ways of creating and maintaining the aforementioned green areas through the participation of both government and private sector or the use of participative management involving municipality and community. It aims at better utilization and administration of these areas, thus avoiding environmental degradation. Lastly, it analyzes the green areas of Teresina categorized by zones

Em Teresina/PI existem muitas áreas verdes intituladas de parques ambientais, bosques ou hortos. A maioria de tais áreas encontra-se abandonada pelo poder público e pela população do entorno, apesar de representar importantes instrumentos de conservação ambiental e de melhoria no clima urbano. Essa realidade é consubstanciada, principalmente, pela inaplicabilidade da legislação referente a áreas verdes, tanto na própria criação da área como na sua manutenção. Em grande parte, são criadas indiscriminadamente e, sem a feitura do plano de uso para sua administração, além da ausência de incentivos para uma educação ambiental direcionada à população do entorno. Isso vem provocando a degradação dessas áreas, manifestada, principalmente, através da poluição, além da desafetação das mesmas para construção de conjuntos habitacionais. Para melhor compreensão do tema buscou-se através da história analisar a origem dessas áreas verdes. Depois foi enfocada a legislação correlata. Foram apontados meios para a criação e manutenção dessas áreas verdes através da participação tanto do poder público como da iniciativa privada, através de uma gestão participativa entre Município e coletividade, objetivando um melhor aproveitamento e administração dessas áreas, evitando, dessa forma, a degradação ambiental das mesmas. Por último, foram analisadas as áreas verdes de Teresina divididas por zona
Keywords: Environmental geography; Geografia ambiental; Gestão ambiental; Degradação ambiental; Políticas públicas; Legislação; Teresina (PI)